1993
DOI: 10.1016/s0022-5347(17)36103-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus 16 Transcription in Human Prostate Tissue

Abstract: Previously we demonstrated human papillomavirus type 16 DNA in a high proportion of benign hyperplastic (BPH) and cancerous (CaP) prostate specimens using the polymerase chain reaction (PCR). While these data designate the prostate as a possible reservoir for sexual transmission of HPV, an etiological role for the virus in prostatic neoplasia is uncertain. Since transcription of the E6/E7 genes of HPV 16 is essential for both viral replication and cellular transformation, we sought to assess the transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Most investigations reported a high frequency of HPV infection in BPH and PCa samples (McNicol and Dodd, 1991;Silvestre et al, 2009;Aghakhani et al, 2011), other investigations found a possible association between HPV and prostate carcinogenesis (Silvestre et al, 2009). On the other hand, wide ranges of studies are not clearly understood any association between HPV infection and prostate carcinogenesis and refuse the causal role of HPV infection in progression of BPH (Dodd et al, 1993;Noda et al, 1998;Leiros et al, 2005;Gazzaz and Mosli, 2009;Aghakhani et al, 2011;Chen et al, 2011;Smelov et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Most investigations reported a high frequency of HPV infection in BPH and PCa samples (McNicol and Dodd, 1991;Silvestre et al, 2009;Aghakhani et al, 2011), other investigations found a possible association between HPV and prostate carcinogenesis (Silvestre et al, 2009). On the other hand, wide ranges of studies are not clearly understood any association between HPV infection and prostate carcinogenesis and refuse the causal role of HPV infection in progression of BPH (Dodd et al, 1993;Noda et al, 1998;Leiros et al, 2005;Gazzaz and Mosli, 2009;Aghakhani et al, 2011;Chen et al, 2011;Smelov et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A secondary adult human prostate epithelial cell culture, on transfection with a plasmid containing the entire type 18 HPV genome, acquired an indefinite, life span in culture but did not undergo malignant conversion (267). Thus, although there are strong arguments in favor of the prostate being an important reservoir for the transmission of HPV (18,101,282,333,350), the involvement of HPV in the pathogenesis of prostate cancer is still a subject of great controversy. For example, two laboratories with extensive experience in HPV research recently tested specimens from two populations with different risks of prostate carcinoma, using three different PCR assays and two serologic assays for HPV.…”
Section: Human Prostatementioning
confidence: 99%
“…The association between HPV and cancer of the prostate is discussed e.g. by Dodd et al [1993], Martinez-Fierro et al [2010] as well as by Lin et al [2011].…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, Dodd et al [1993] underlines that the human prostate gland may act as a reservoir of HPV. In his book, Zur Hausen [2011] declares that the role of HPVs is unclear in the develop-ment of the prostate cancer.…”
Section: Cancer Of the Prostate Glandmentioning
confidence: 98%
See 1 more Smart Citation